Perancangan Mesin Penghalus Sampah dengan Menggunakan Prinsip Inovasi Frugal Di Pondok Pesantren Cipasung Tasikmalaya - Wahyu Teri Aripin; Hilman Mutaqin (Cipasung Techno Pesantren: Jurnal Ilmiah, 2023)
Cipasung Islamic Boarding School is one of the Islamic Boarding Schools that still carries out waste disposal activities with an open dumping system. The system causes various losses such as no added value for Islamic boarding schools and environmental pollution at the Final Disposal Site. One solution to the waste problem is to manage it into waste briquettes. After drying and chopping, it is then mashed with a garbage crusher machine. Refining machines sold in the market are quite expensive, therefore, a waste-refining machine is designed with the principle of saving innovation. These innovations create products that are cheaper than existing products. The Design Process Using Machine Design Procedures. Making machine drawings using LibreCAD and Blender software. The price of the machine is calculated using the bill of materials. Machines designed using materials available in the market such as used drums, angle iron, large knives and small power dynamos. Has the same capacity and speed of waste processing as machines sold in the market, and has a lower price.